Spectrum dan Spectrum Laplacian pada Graf Mahkota - Umam, Khoirul (KALBISCIENTIA Jurnal Sains dan Teknologi, 2019)
Crown Crown () is a graph that has the number of vertices and the number of edges are with , integers. Suppose that are eigen values of a matrix and are the multiplicity of each , so the spectrum of a graph can be expressed as a matrix whose line elements are in the first row, and in the second row. In this paper, we will discuss spectrums from adjacency matrices and laplacian matrix spectrums of